2016
DOI: 10.1113/ep085556
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated haemodynamic and neural responses to involuntary contractions induced by whole‐body vibration in normotensive obese versus lean women

Abstract: New Findings r What is the central question of this study?In obesity, the exaggerated blood pressure response to voluntary exercise is linked to hypertension, yet the mechanisms are not fully elucidated. We examined whether involuntary contractions elicit greater haemodynamic responses and altered neural control of blood pressure in normotensive obese versus lean women. r What is the main finding and its importance? During involuntary contractions induced by whole-body vibration, there were augmented blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 66 publications
(80 reference statements)
0
22
0
1
Order By: Relevance
“…NOx decreases systolic BP and AIx reducing the vascular tone of small arteries [84]. Second, the mechanical oscillatory contractions during vibration serve as an active muscle pump and increase stroke volume, probably enhancing venous return and preload [85]. Third, total peripheral resistance to blood flow increases during body vibration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOx decreases systolic BP and AIx reducing the vascular tone of small arteries [84]. Second, the mechanical oscillatory contractions during vibration serve as an active muscle pump and increase stroke volume, probably enhancing venous return and preload [85]. Third, total peripheral resistance to blood flow increases during body vibration.…”
Section: Discussionmentioning
confidence: 99%
“…WBVT could be prescribed without additional exercise in the initial stages of a weight loss program, due to the limited stress upon joints and the GH-mediated stimulation of metabolism, without provoking an excessive fatigue [63,85]. Passive vibrations do not involve voluntary movement and require a lower contribution of central command [98].…”
Section: Conclusion and Recommendations For Future Researchmentioning
confidence: 99%
“…Dipla et al . () assigned normotensive lean and obese women to 6 min of PV (frequency 25 Hz, amplitude 6 mm) with the knee flexed at 18° angle. Greater HR increases were noted during PV than control standing without PV in both lean and obese women (no between‐group differences).…”
Section: Acute Effects Of Passive Vibration On Hrvmentioning
confidence: 99%
“…Regular exercise has been shown to reduce body fat as well as protect against cardiovascular diseases associated with obesity [ 6 , 7 , 8 ]. On the other hand, obesity produces excessive increases in arterial blood pressure (BP) during exercise [ 9 , 10 ]. These augmented BP responses may increase the risk of cardiac events associated with exercise (e.g., stroke, acute myocardial infarction) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that hemodynamic responses mediated by the MMR are not augmented and the muscle vasodilatory responses are not altered in obese women. In contrast, another study investigated that a whole-body vibration caused exaggerated BP responses in normotensive obese women and suggested that this excessive response may be attributed to a mechanoreflex disfunction [ 9 ]. The inconsistency in BP response induced by the MMR activation could be due to differences in muscle mass (i.e., handgrip exercise vs. whole body exercise).…”
Section: Introductionmentioning
confidence: 99%